MEN’S DOMINATION OVER WOMEN IN VICTORIAN SOCIETY AS PRESENTED IN GASKELL’S THE OLD NURSE’S STORY - Kharismawaty, Inggil; Hetami, Fatma; Bahri, Seful (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2018)
Men and women have a different position in society. The men are in the upper position than the women. It can be seen in several aspects of life that men hold more power than women such as in social, economic, and cultural. Men’s position as an upper class of society gives them the power to dominate women. This study aims at investigating men’s domination over women and women’s characters’ reaction to deal with it. The objectives of this study are; 1) to investigate how men’s domination over women is presented in Gaskell’s The Old Nurse’s Story, and 2) to investigate what are women’s characters reactions to men’s domination over women as it is presented in Gaskell’s The Old Nurse’s Story. This is a qualitative study which the data had taken are in the form of words, phrases, and sentences. The data had interpreted and reported descriptively. Gaskell’s The Old Nurse’s Story was used as the object of the study. Moreover, Feminist Criticism was applied in this study. Then, to support the analysis, the writer used radical feminist theory by Betty Friedan. The analysis was conducted by analyzing the elements of a short story, then relating the data based on Friedan’s theory of radical feminism. The result of the study shows that 1) men’s domination over women in Victorian society is presented through power inequality, social hierarchy, and social competition. 2) women’s characters reaction to men’s domination can be seen through the character of Hester and the two ladies Furnivall, they are being female, androgynous, supporting as well as rejecting the term biological motherhood.